Comportamentos de coping no contexto da hospitalização infantil - Motta, Alessandra Brunoro; Perosa, Gimol Benzaquen [UNESP]; Barros, Luisa; Silveira, Kelly Ambrósio; Lima, Ana Sofia Da Silva; Carnier, Luciana Esgalha [UNESP]; Hostert, Paula Coimbra Da Costa Pereira; Caprini, Fernanda Rosalém (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2015)
Child hospitalization needs to cope with the stressors that cause anxiety and suffering. Aiming at describing the coping behaviors of hospitalized children and their relationships to age, sex and the reason for hospitalization, 148 responses of children aged 6-12 were analyzed (M = 9.5 years old) to the Coping with Hospitalization Scale, from an integrated database. The results were analyzed by descriptive and inferential statistics. Taking some medicine, talking, watching television, praying and playing were the most referred to behaviors. There was a correlation between the coping behaviors and the differences caused by the hospitalization reason. Girls tend to sing more, and demonstrated more crying, sorrow and fear than boys. There were no differences as to age, but persuasion behavior decreases in older children. We suggest that sex, hospitalization reason and age have to be considered in interventions on coping with hospitalization.

A criança hospitalizada precisa lidar com estressores que geram ansiedade e sofrimento. Com o objetivo de descrever comportamentos de coping de crianças hospitalizadas e suas relações com idade, sexo e motivo da hospitalização, foram analisadas respostas ao Instrumento de Avaliação das Estratégias de Enfrentamento da Hospitalização de 148 crianças (6-12 anos, M = 9,5 anos), a partir de um banco de dados integrado. Os resultados foram analisados por estatística descritiva e inferencial. Tomar remédio, conversar, assistir televisão, rezar e brincar foram os comportamentos mais referidos. Houve correlação entre comportamentos de coping e diferenças decorrentes do motivo da hospitalização. Meninas cantam mais e referiram mais choro, tristeza e medo do que meninos. Não foram verificadas diferenças em relação à idade, mas o comportamento de chantagem diminuiu em função da maior idade. Sugere-se que variáveis como sexo, motivo da hospitalização e idade sejam consideradas em intervenções com foco no coping da hospitalização.
Coping behaviors in the child hospitalization context
Keywords: Coping; Child hospitalized; Hospitalization; Coping; Criança hospitalizada; Hospitalização